Detection and characterization of listeria monocytogenes in São Jorge (Portugal) cheese production - Kongo, J. M. (2006)
Listeria monocytogenes is a foodborne pathogen that can cause serious invasive disease in humans. Because human listeriosis cases have previously been linked to consumption of contaminated cheese, control of this pathogen throughout the cheese production chain is of particular concern. To understand the potential for L. monocytogenes transmission via Sa˜o Jorge cheese, a Portuguese artisanal cheese variety that bears a Protected Denomination of Origin classification, 357 raw milk, curd, natural whey starter, and cheese samples representative of the production chain of this cheese were collected over one year and tested for the presence of L. monocytogenes and selected physicochemical parameters. Although neither L. monocytogenes nor other Listeria spp. were detected in whey, curd, or cheese samples, 2 of the 105 raw milk samples analyzed were positive for L. monocytogenes. These 2 raw milk isolates represented a ribotype that has previously been linked to multiple human listeriosis outbreaks and cases elsewhere, indicating the potential of these isolates to cause human listeriosis. On average, physicochemical parameters of Sa˜o Jorge cheese ripened for 4 mo presented values that likely minimize the risk of L. monocytogenes outgrowth during ripening and storage (mean pH = 5.48; mean moisture = 37.79%; mean NaCl concentration = 4.73%). However, some cheese samples evaluated in this study were characterized by physicochemical parameters that may allow growth and survival of L. monocytogenes. Even though our results indicate that raw milk used for Sa˜o Jorge cheese manufacture as well as finished products is rarely contaminated with L. monocytogenes, continued efforts to control the presence of this pathogen in the Sa˜o Jorge cheese production chain are urged and are critical to ensure the safety of this product.